Qualitative Profiling of Antimalarial Compounds from Endophytic Fungi Associated with Rhizophora mucronata - Suhendar, Usep; Fawziah, Rieskha; Lohita Sari, Bina; Yoshida Srie Rahayu, Sata; Sulastri, Lilik; Wulandari, Ratna; Anisa, Dede; Namira, Raisa (Universitas Nusa Bangsa, 2025)
Malaria remains one of the deadliest infectious diseases worldwide, underscoring the urgent need for novel antimalarial sources. Endophytic fungi associated with mangrove roots of Rhizophora mucronata represent promising candidates, as they are capable of synthesizing secondary metabolites such as alkaloids, flavonoids, and terpenoids with known antiplasmodial activity. This study aimed to qualitatively identify antimalarial bioactive compounds from endophytic fungal extracts previously exhibiting the highest heme polymerization–inhibition activity. Fungal isolates were fermented in liquid medium for 21 days and extracted with ethyl acetate. The extracts were profiled by Thin-Layer Chromatography (TLC) using two solvent systems: n-hexane : ethyl acetate (5:1) and dichloromethane : methanol (10:1). Band visualization was performed under UV light (254 nm and 366 nm) and with semi-specific reagents (Dragendorff and citro-boric), followed by Rf value comparison. TLC analysis revealed blue-green fluorescent bands corresponding to flavonoids and brown-orange bands indicative of alkaloids, with optimal Rf values of 0.46 (n-hexane : ethyl acetate) and 0.54 (dichloromethane : methanol). These findings confirm the presence of key antimalarial compound classes in the endophytic fungal extract, supporting its potential as a coastal bioresource for drug discovery and development.